Governing people, governing places: advancing the Protean environmental state in China. Issue 5 (2nd September 2020) - Flynn, Andrew; Xie, Linjun; Hacking, Nick
ABSTRACT: Since the 1990s, the unprecedented rate of economic change in China has created a series of critical policy challenges for both central and subnational states. How these policy challenges are conceived will determine how and when they can be solved. There is a growing interest, in particular, in the problematic issues of welfare, resource management and environmental pollution and how those are managed by the local state. In this study, we analyse the ongoing development of the Sino-Singapore Tianjin Eco-City (SSTEC) using the lens of the 'Protean Environmental State.' This multi-faceted perspective on development is one that we have further progressed after more than a decade's research on China's multi-level environmental governance. In this paper, we concentrate on regulatory and enhancement activities. Our work draws upon fieldwork in and around the SSTEC and highlights the problematic nature of reforms to the environmental state. Ultimately, we explore the inherent and ever-shifting tensions between economic and environmental imperatives in relation to the emerging governance of people and of economic development in present-day China.